(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
Advanced oxidation process (AOPs) prepares one of the important methods to degradation and removal the organic pollutants from aqueous solutions. AOPs method depends on the formation of hydroxyl radicals from hydrogen peroxide with a catalyst. In this work we relied on Fenton reaction to removes the Methylene Blue (MB) using natural magnetite as catalyst. The time for degradation of MB solutions (volume 25ml) in the different concentrations (20, 40, 60, 80) ppm was determined. The maximum degradation of MB in the solution was achieved after 24h with UV irradiation and without any additions, the maximum degradation of MB with UV and in addition of magnetite was achieved after 18h, and with UV + H2O2 the process was took up 3.5h, when adding magnetite + H2O2 and using UV the process of degradation of MB was completed after 2.5 hour. The optimal conditions of the degradation process of MB were: when adding 0.15g magnetite + 0.2ml H2O2 using UV, and that for 25 ml value of MB.